Building scaffolding by teaching music in preschool education - Moreno, Davys (2021)
Early Childhood Education in both Portugal and Chile is considered the first stage of Basic Education in the process of lifelong education. Both countries have quite a few similarities as to the curricular bases for this level of education, namely as to the contents related to artistic education, music and musical expression. Unfortunately, in both countries there are limitations in the skills of kindergarten teachers which prevent the proper development of these artistic areas among children. In order to overcome these limitations, an experimental research project was developed in Chile between the years 2012 and 2013, which included a musical training programme through the methodology of Shinishi Suzuki. The aim was to improve the skills of kindergarten teachers in music, including learning the violin instrument, in 3 kindergartens in the network of the "Junta Nacional de Jardines Infantiles de Chile" (JUNJI) belonging to a city in that country. After this musical training programme, the kindergarten teachers replicated the knowledge obtained in an intervention with the children of their groups (Experimental Group), based on the application of the Suzuki methodology. To evaluate this project, the results of the blind application of the IEPA standardised test "Instrumento de Avaliación para el Aprendizaje" were compared, at the beginning and at the end of the intervention, to the children belonging to both the Experimental Group and the Control Group, the latter consisting of all the children from the JUNJI Network kindergartens who did not participate in the intervention. The results showed significant differences in terms of the development of communication and socialisation, using the evaluation carried out with the IEPA instrument, between the children of the Experimental Group and those of the Control Group, with the Experimental Group's score being higher than that of the Control Group. We were led to conclude that by boosting the skills of the kindergarten teachers, with the application of a Music Training Programme based on the Suzuki methodology, which they then replicated to the children, an improvement in the areas of communication and socialisation of these children was observed. This study is a real contribution to future planning as far as teachers training is concerned, proposing its replication in other contexts, namely in Portugal.